2008
DOI: 10.1371/journal.pone.0001612
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3 Promoter Demethylation Reveals the Committed Treg Population in Humans

Abstract: BackgroundNaturally occurring thymus derived regulatory T cells (Tregs) are central in the maintenance of self-tolerance. The transcription factor FOXP3 is crucial for the suppressive activity of Tregs and is considered the most specific marker for this population. However, human non regulatory T cells upregulate FOXP3 transiently upon activation which calls for other means to identify the Treg population. Since epigenetic mechanisms are involved in the establishment of stable gene expression patterns during c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
160
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(177 citation statements)
references
References 41 publications
13
160
0
1
Order By: Relevance
“…2A). A similar trend was also observed in the relative presence of the Treg-cell-specific demethylated region (TSDR), an epigenetic mark within the foxp3 gene proposed to identify stable, tTreg cells [27]. We analysed two healthy male donors and found that the average TSDR expression in SEB-specific CD4 + CD25 + CD134 + CD39 + T cells was 28.80%, which corresponds to approximately five times the average expression in SEB-specific CD4 + CD25 + CD134 + CD39 − T cells (6.19%).…”
Section: Resultssupporting
confidence: 59%
“…2A). A similar trend was also observed in the relative presence of the Treg-cell-specific demethylated region (TSDR), an epigenetic mark within the foxp3 gene proposed to identify stable, tTreg cells [27]. We analysed two healthy male donors and found that the average TSDR expression in SEB-specific CD4 + CD25 + CD134 + CD39 + T cells was 28.80%, which corresponds to approximately five times the average expression in SEB-specific CD4 + CD25 + CD134 + CD39 − T cells (6.19%).…”
Section: Resultssupporting
confidence: 59%
“…These findings suggest that the epigenetic modification of the Foxp3 gene is critical for the stable expression and suppressive function of Treg cells. These observations have also been confirmed in cord blood Treg cells 74 and peripheral Treg cells 75 in humans, where the latter transient expressers of FOXP3 bear a partially methylated TSDR. 75 Consistent with this FOXP3 þ regulatory T cell regulation and plasticity Y Gao et al notion, a TcR response element was found in the first intron of the Foxp3 gene that is located within this CNS region 76 and also Est-1 binding sites, which are important for positively regulating Foxp3 transcription.…”
Section: Epigenetic and Transcriptional Regulation Of Foxp3supporting
confidence: 57%
“…These observations have also been confirmed in cord blood Treg cells 74 and peripheral Treg cells 75 in humans, where the latter transient expressers of FOXP3 bear a partially methylated TSDR. 75 Consistent with this FOXP3 þ regulatory T cell regulation and plasticity Y Gao et al notion, a TcR response element was found in the first intron of the Foxp3 gene that is located within this CNS region 76 and also Est-1 binding sites, which are important for positively regulating Foxp3 transcription. 77,78 The TSDR also overlaps with the binding site for the transcription factor cyclic AMP (cAMP) response element-binding, where an increase in TSDR methylation negatively correlates with cAMP response elementbinding and Foxp3 expression.…”
Section: Epigenetic and Transcriptional Regulation Of Foxp3supporting
confidence: 57%
“…2) because cell cycling increases the expression of certain methylating enzymes such as DNA methyltransferase 1 (DNMT1), which could interfere with stable Foxp3 expression (13,22,23). Complete demethylation of CpG motifs at the foxp3 locus was shown to correlate with a stable human (24,25) and mouse Treg phenotype (13). Pharmacologic inhibition of the DNMT1 activity and knocking down or ablating DNMT1 gene markedly increased the efficacy of induction and stability of Foxp3 expression (13,22,23).…”
Section: Resultsmentioning
confidence: 99%